Lithophylloideae and Mastophoroideae (Corallinales, Rhodophyta) from the Brazilian continental shelf - Henriques, Maria Carolina; Riosmena-Rodríguez, Rafael; Coutinho, Luana Miranda; Figueiredo, Marcia A. O. (Phytotaxa, 2014)
Brazilian continental shelf is rich in rhodolith beds and it has a relevant role as a critical ecosystem for conservation. However, we do not know the taxonomy of the rhodolith forming species and because of that we analysed samples from the REVIZEE project in which morpho-anatomical analysis was used to identify Lithophylloideae and Mastophoroideae species. We found Titanoderma pustulatum; Lithophyllum stictaeforme; Lithophyllum corallinae, Hydrolithon breviclavium, Hydrolithon onkodes and Spongites fruticulosus. This is the first detailed description of T. pustulatum from Brazil and S. fruticulosus from the Atlantic Ocean, the first record of H. breviclavium in the Atlantic Ocean and of H. onkodes in Brazilian water. L. corallinae was found 250 m deep—that is a new Coralline algae depth record for Brazilian waters. This study contributes to the understanding of the diversity in Brazilian continental shelf and indicates the importance of future systematic studies. This knowledge is relevant to guide conservation programs and evaluation of impacts.